The relation of business complexity to audit fee on non-financial company - Djoko Dewantoro, Heidiana Rachma Ningtyas, (Opción, 2020)
This study aims to examine the influence of business complexity which includes merger and acquisition, company size, Chief Executive Officer (CEO) compensation, and foreign employee to audit fee on the non-financial company. This study uses a saturation sampling method with 171 samples. The data which are used for this study is a secondary data collected from audited annual reports. The result of multiple regression analysis shows that the variables which are merger and acquisition, company size, and CEO compensation significantly influenced the audit fee. In conclusion, Mergers and acquisitions, company size, CEO compensation, and foreign employees influenced the audit fees.